The optimization of multi-walled carbon nanotubes surface modification via nitric acid oxidation for DNA immobilization - Shahidah Arina Shamsuddin (School of Nano Electronic Engineering, Universiti Malaysia Perlis, 2014)
This thesis discussed on the optimization of MWCNTs surface modification via nitric acid oxidation for DNA immobilization. After acid oxidation treatment, the impurities in multi-walled carbon nanotube (MWCNTs) such as carbonaceous and metal catalyst particles are successfully reduced as has been analyzed by energy dispersive x-ray spectroscopy (EDS), x-ray diffraction (XRD) and thermogravimetric analyzer (TGA). Acid oxidation will caused to the opening of MWCNTs tips and structural defects formed on the MWCNTs surface due to the acid attack. Oxygen containing functional groups, mainly, carboxylic group (COOH) has been introduced on the MWCNTs opened tips and at the defect sites which are useful to interact with other molecules, in this case, aminated-ssDNA probe. The results from fourier transform infrared spectroscopy (FTIR) and Raman Spectroscopy have shown that the COOH amount is depended on the MWCNTs structure defects. Meanwhile, cyclic voltammetry (CV) results have indicated that the immobilization current is directly proportional to the COOH amount. However, structure defect will affect to the immobilization current when ID/IG ratio is increased. The acid oxidation parameter should be optimized, thus the amount of COOH can be increased with the minimal structure defect. Therefore, the main goal to have a maximum immobilization current can be achieved. L9 Taguchi orthogonal array has been used to optimize the acid oxidation parameters. From the result, 5 M of nitric acid concentration, 120 C of treatment temperature and 6 hours of treatment time are selected as the most optimum combination of acid oxidation parameters. The percentage influence of each main factor is also calculated to be 46%, 35% and 18% for nitric acid concentration, treatment time and treatment temperature, respectively. The improvement is happened to be 11.6% of increment in the immobilization current.